Intermodal Passenger Transportation Industry: Development Factor in The Tourism Sector - Mohammad Shahparan; Akmaljon Odilov; Shokirov Firdavsbek; Kuvandikov Sardor; Artem Klykov (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: The purpose of this research paper is to highlight the importance of intermodal passenger transport in the tourism sector. This paper describes the intermodal transportation system and how it has developed the tourism sector. Research methods: Qualitative methods are used in this paper. Data was collected from different online sources, such as Streamline journals, related to transport and tourism. Results and discussion: The result of this research paper shows that the development of the tourism sector, along with the intermodal passenger transportation sector, which is the key factor in the development of the tourism sector. This research paper connects the intermodal transportation system to the tourism sector. The intermodal transportation industry is one of the critical sectors of development in the tourism sector. The use of intermodal transportation is a typical daily routine for tourism. Implication: The advice given to the future researcher and transportation, travel, and tourism company to highlight the intermodal passenger transportation system to add more advantages to both the transport company and the travel and tourism company. Through this paper, future researchers can easily connect intermodal transportation to the tourism sector. Keywords: Intermodal, Transportation, Tourism, Place, Sector.